2014
DOI: 10.1002/lt.23960
|View full text |Cite
|
Sign up to set email alerts
|

Effect of remote ischemic postconditioning on patients undergoing living donor liver transplantation

Abstract: The aim of this study was to evaluate the protective effect of remote ischemic postconditioning (RIPostC) on graft function and acute kidney injury (AKI) after living donor liver transplantation (LT). Recipients undergoing elective living donor LT were randomly assigned to either the RIPostC group or the control group. Immediately after reperfusion, 4 cycles of ischemia and reperfusion lasting for 5 minutes each were performed on 1 upper limb in the RIPostC group. Graft function was assessed through evaluation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 52 publications
0
41
0
1
Order By: Relevance
“…The diverging results could be explained by the fact that we used a porcine model with an ischemic event in contrast to healthy men with no ischemic event. Furthermore, RIC did not affect postoperative PT and international normalized ratio (INR) in a randomized controlled trial on living donor liver transplantation (Kim et al, 2014). However, RIC increased PT and INR when administered repeatedly in patients hospitalized for aneurysmal subarachnoid hemorrhage, Thrombin generation in systemic blood samples from the control and intervention group during reperfusion: lag time, time-topeak, peak thrombin, and endogenous thrombin potential (ETP) presented as means with SD.…”
Section: Discussionmentioning
confidence: 99%
“…The diverging results could be explained by the fact that we used a porcine model with an ischemic event in contrast to healthy men with no ischemic event. Furthermore, RIC did not affect postoperative PT and international normalized ratio (INR) in a randomized controlled trial on living donor liver transplantation (Kim et al, 2014). However, RIC increased PT and INR when administered repeatedly in patients hospitalized for aneurysmal subarachnoid hemorrhage, Thrombin generation in systemic blood samples from the control and intervention group during reperfusion: lag time, time-topeak, peak thrombin, and endogenous thrombin potential (ETP) presented as means with SD.…”
Section: Discussionmentioning
confidence: 99%
“…LRIP is easy for operation, while its mechanisms are unclear [36,37]. The role of inflammation and oxidative damage on stroke and cardiovascular disease pathogenesis is very important and has been studied by lots of researchers [20,21,38,39].…”
Section: Discussionmentioning
confidence: 99%
“…They showed an improvement in GFR and renal perfusion in the experimental group, although the animals were recovered for only 10 h. These authors also measured haem oxygenase 1 and NGAL excretion and inflammation markers, but demonstrated no difference between the groups, which may be due to the short recovery period 27 . Two randomized studies 28,29 comparing living donor transplant recipients have shown that IC has no effect on renal function. This could be explained by the minimal ischaemic injury sustained by the organs.…”
Section: Discussionmentioning
confidence: 99%